Sharia Financial Institutions, Synergy, and Their Role in Empowering MSMEs in Badung Regency - Setia Utami, Indah; Hidayati, Berlina; Subekti, Rini; Ria Viana Praningtyas, Elisabeth (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
MSMEs have a very large contribution to the Indonesian economy. The potential for MSMEs development is no exception in Badung Regency as the region with the largest local and international tourist destination in Indonesia. MSMEs are the key to accelerating Indonesia's sharia economy. Synergy and collaboration between various parties are needed to achieve the government's target of making Indonesia the center of the world's halal industry. This research was conducted to determine the role of Sharia Financial Institutions and their synergy efforts with related parties in empowering MSMEs. The research was conducted using a qualitative method to explore in-depth information from various parties using the focus group discussion method. This research is the first research to qualitatively analyze the role and synergy of Sharia Financial Institutions in the development of MSMEs in Badung Regency. The research results show that the role and synergy of sharia financial institutions are not yet optimal, there are various obstacles faced and more massive outreach, collaboration, and synergy efforts with various parties are needed to increase the role of sharia financial institutions in empowering MSMEs. This study concludes that increasing cooperation between Sharia Financial Institutions, the government, and MSMEs is very important, especially in the form of more massive socialization, more in-depth training, and ongoing assistance, to expand market access.